The Development of Thai Writing Communication for Secondary Students in the Non-Formal and Informal Education Center by Using Mind Mapping and Drills - สีสุดทา, เชิญพร; ฤทธิเดช, ประสพสุข; กุลสุวรรณ, กัลยา (Journal of Roi Et Rajabhat University, 2019)
The purposes of this study were : (1) to develop Thai writing communication activities for students of the Non-Formal and Informal Education Center by using mind mapping and drills with the efficiency criterion of 80/80, (2) to examine an effectiveness index of Thai writing communication activities, (3) to compare pre-test and post-test scores in Thai writing communication of students by using mind mapping and drills, and (4) to measure students' satisfaction toward the Thai writing communication activities using of mind mapping and drills. The sample was selected using the cluster random sampling in the second semester of 2017 academic year comprising 40 secondary students from Non-Formal and Informal Education Center, Khamsakeasang Khamsakeasang district, Nakhon Ratchasima province. The research tools included: 1) 8 lesson plans, 2) achievement tests 3) assessment form of Thai writing communication, and 4) a satisfaction questionnaire. The statistics used were percentage, mean, standard deviation, and t-test (Dependent Sample) for hypothesis testing. The results of the study were as follows: 1) The efficiency of Thai writing communication activities using mind mapping and drills was 83.0/85.83 2) The effectiveness index of Thai writing communication activities using mind mapping and drills was equal to 0.7166 3) The achievement, it was found that posttest score was higher than the pretest at .05 level of significance. 4) Students’ satisfaction toward the Thai writing communication activities using mind mapping and drills was overall at a high level. ( = 4.66, S.D. = 0.54)